Ecological studies of aquatic moss pillars in Antarctic lakes 3. Light response and chilling and heat sensitivity of photosynthesis - Kudoh, Sakae; Kashino, Yasuhiro; Imura, Satoshi (National Institute of Polar Research, 2003)
P(論文) The light-photosynthesis relation was measured using a PAM chlorophyll fluorometric method in a moss, Leptobryum sp., which is the primary component of aquatic moss pillars, in cultured Leptobryum sp. on an agar plate, and in both aquatic and terrestrial forms of Bryum pseudotriquetrum. The morphology of the plate-cultured Leptobryum sp. was clearly different from the sample growing on an aquatic moss pillar; the leaves and shoots were considerably thickened and enlarged in the former. In spite of the great difference of morphology, photosynthetic light responses such as light-PS II yield, -non-photochemical quenching and the relative rate of electron transport of both samples were nearly the same. On the other hand, the responses of B. pseudotriquetrum collected from a moss pillar and terrestrial habitat differed greatly. Light-PS II yield and light-ETR relationships of the Leptobryum sp. showed rather shade-plant type response, low effective PS II yield at any light intensity and low maximum ETR with low light saturation point, while B. pseudotriquetrum from a terrestrial habitat showed rather 'sun-plant' type responses. Aquatic B. pseudotriquetrum showed the lowest values of effective PS II yield and ETR at almost all light intensities among the present samples. Chilling/heating stress was experimentally added to the aquatic Leptobryum sp., and it was found that both maximum and effective yield of PS II showed quite narrow and cryophilic relationships with treatment temperatures. These photosynthetic features observed in the Leptobryum sp., shade-plant type light response and very naive sensitivity to the changes of temperature, suggest that the species can perform photosynthetic growth within the aquatic habitat; however, it cannot survive or prevail in the terrestrial habitat in severe East Antarctica. departmental bulletin paper